2019
DOI: 10.3390/s20010073
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Temperature Sensor Integration into E-Textiles Using Different Industrial Yarn Fabrication Processes

Abstract: Textiles enhanced with thin-film flexible sensors are well-suited for unobtrusive monitoring of skin parameters due to the sensors' high conformability. These sensors can be damaged if they are attached to the surface of the textile, also affecting the textiles' aesthetics and feel. We investigate the effect of embedding flexible temperature sensors within textile yarns, which adds a layer of protection to the sensor. Industrial yarn manufacturing techniques including knit braiding, braiding, and double coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…d Photo of the fabricated device [ 184 ]. e Concept of the flexible temperature sensor embedded within the fibres of a textile yarn [ 185 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…d Photo of the fabricated device [ 184 ]. e Concept of the flexible temperature sensor embedded within the fibres of a textile yarn [ 185 ] …”
Section: Resultsmentioning
confidence: 99%
“…Due to its high consistency, it is very suitable for non-existent monitoring of skin temperature, which significantly benefits patients and medical staff. Lugoda et al [ 185 ] used different industrial yarn fabricating processes to integrate flexible temperature sensors into fabrics, and studied the sensing effect of embedding flexible temperature sensors in textile yarns. The bending resistance and repeatability of the temperature sensor embedded in the yarn are verified.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the step-response time of the temperature sensing E-yarns were not investigated in this work. Previous studies on similar sensors [34] have shown these step response times to be very short, with the longest times reported being on the order of seconds.…”
Section: E-yarn Functionality When Embroidered Onto the Cycling Suitmentioning
confidence: 91%
“…Various designs have been proposed for temperature monitoring with smart socks, both for diabetic and for healthy patients. Concerning the diabetic ones, temperature sensor integration technology in smart textiles [55] and TSS (temperature-sensing socks) technology was proposed, which is able to detect temperature variations in the feet. These temperature variations are good predictors of foot ulceration in diabetics, a condition that can lead to complications, even to amputation.…”
Section: Central Unit Gathering Data and Forwarding To External Devicementioning
confidence: 99%